Checkpoint Controls and Targets in Cancer Therapy - Siddik, Zahid H. (Cancer Drug Discovery and Development, 2009)
There is no question that loss of cell cycle checkpoint regulation is an intrinsic characteristic of cancer. However, many tumors retain parallel checkpoint pathways that are activated by antitumor agents and facilitate therapeutic response. Failures in these therapy-linked checkpoint controls are closely associated with cancers that are highly resistant to therapeutic interventions. Checkpoint Controls and Targets in Cancer provides present-day mechanistic understandings of how multiple sets of proteins orchestrate cell cycle progression, discusses critical checkpoint controls that are evaded for cancer development, focuses on checkpoint pathways associated with antitumor effects, and identifies specific checkpoint regulators for targeting with small molecules in the clinical management of cancer. These aspects of cell cycle checkpoints are articulated critically by renowned experts from both academia and industry, and new concepts are forwarded that challenge existing dogmas. Collectively, Checkpoint Controls and Targets in Cancer provides a unique collection of insightful contributions, which are timely and offer significant interest and appeal to basic, translational and clinical scientists.